Age related differences in agility during a training season in youth elite soccer players - Bidaurrazaga-Letona, I.; Carvalho, H. M.; Lekue, J. A.; Gil, S. M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
INTRODUCTION: Agility performance is of relevance in soccer given its multidirectional nature and may be an indicator of performance (1). Therefore, the aim of this study was to examine the age group variation in agility responses within a training season in youth soccer players. METHODS: Thirty-three youth soccer players of the professional soccer club Athletic Club of Bilbao participated in this study. The sample included players of the under-11 (n=18) and under-13 teams (n=15), aged at baseline 10.4 ± 0.3 and 11.98 ± 0.77 years, respectively. Age at peak height velocity (APHV) and maturity offset were estimated at the start of the season. Player`s agility, body mass and stature were evaluated on two occasions during the training-season: at the beginning of the season in October 2009 and in June 2010, the end of the season. The agility protocol used was a modification of the Barrow zig-zag run test (2). Multilevel linear regression analysis was used to estimate individual changes across the season, and the differences in changes between competitive age groups. Logarithmic transformations of dependent and independent variables were used to analyze changes in percentage. RESULTS: All maturity offset values were negative indicating that the sample was behind the age at PHV. Increases in body size over the training period were significant (p < 0.05), reflecting pubertal growth. The multilevel models showed that the agility performance presented a significant improvement (p < 0.01) suggesting a possible beneficial effect of soccer specific training in agility. Older players had significantly better performances (p < 0.01), but the rate of improvements appeared to be similar in both age groups. The changes in agility performance were independent from the maturity offset, as the inclusion of the variable in a separate model was not significant. DISCUSSION: There was an improvement in agility performance, on average. Also, a substantial group age effect on the agility performance pre- and end-season was observed. Older adolescent players appear to perform better compared to younger players but the rate of improvements was similar in both age groups. Since selection in soccer tends to favor early mature boys (3), the differences between groups may be partially attributed to linear growth and gains in muscle mass with age.